Footprints at the window - Naylor, Phyllis Reynolds (Naylor, Phyllis Reynolds. York trilogy, 1981)
Beset by an enemy from within, Dan searches for the gypsies he once knew in York and is led inexplicably into a calamity involving the Black Death in a hostile country among frightened and superstitious people.